Analisis Hak Presiden Ikut Serta Dalam Kampanye Berdasarkan Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilu Di Indonesia - Rehan Fahri Septiawan; Eriton, Muhammad; Amin, Muhammad (Limbago: Journal of Constitutional Law, 2025)
This study analyzes the president's right to participate in political campaigns based on Law Number 7 of 2017 concerning General Elections, as well as its legal implications in the future. The law grants the president and vice president the right to campaign, but it raises debates regarding its limitations and impact on the integrity of elections. This research employs a normative juridical method using statutory, conceptual, historical, and case approaches, with primary and secondary legal materials serving as the basis for analysis. The study focuses on the provisions in the Election Law and General Election Commission Regulation (PKPU) Number 15 of 2023, which regulate the president's campaign rights. Additionally, the research examines legal experts' perspectives on the potential abuse of power if the president actively participates in campaigns, particularly in the context of the 2024 election, where the president is not running but supports a specific candidate. The findings indicate that while the president legally has the right to campaign as stipulated in Article 299 Paragraph (1) of the Election Law, the implementation must comply with other provisions aimed at maintaining neutrality and fairness in the election process. Clear regulations are expected to ensure legal certainty and fairness in the conduct of elections in Indonesia.